(untitled) (Oxford, UK, 2005)
Fascinating and instantly recognisable, flatfishes are unique in their asymmetric postlarval body form. With over 700 extant species recognised and a distribution stretching across the globe this group of fishes are of considerable research interest and provide a major contribution to recreational and commercial fisheries, and to aquaculture, worldwide.
Keywords: Flatfishes,Flatfish fisheries,Cá bơn,Nghề cá bơn